Empowering Education: Unveiling Effective Strategies in School Principal Supervision to Enhance Teacher Professionalism - Novelina Andriani Zega; Nathanael Sitanggang (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The world of education is evolving rapidly, both in terms of technology, teaching methodology, and educational theory. In response to these changes, teachers need to continue to develop their competences to remain relevant and effective in educating students. Teachers are often faced with different contextual challenges, such as large classrooms, students with diverse backgrounds, or less supportive learning environments. Developing teachers' competences can help them cope with these challenges better. This study aims to reveal the principal's leadership strategy in improving teacher professionalism. This research uses a mixed method approach, data sources include all teachers while data collection through interview techniques and documentation. The analysis uses continuous participatory techniques, through the stages of data collection, reduction, presentation, and conclusion drawing. This research used a mixed method with a descriptive qualitative approach. The research data obtained through the research conducted is by using the methods and instruments that the researcher determined on the previous page. This research instrument uses a questionnaire with data analysis techniques to describe the level of principal supervision in improving teacher competence in carrying out learning process activities. The results showed that the principal's strategy in improving teacher professionalism is by conducting training, teacher evaluation meetings, classroom supervision, motivating teachers, giving rewards and giving punishments, and through participatory leadership styles. The success of education cannot be separated from the principal's efforts as a leader in directing and motivating teachers, encouraging and conducting curriculum development training, classroom management strategies, the purpose of this training is to improve teacher professionalism as a behavior change in learning carried out in the classroom. In essence, the success of a leader when applying the form of leadership in life with the principles of time management and work time discipline as a priority scale in realizing maximum performance results. In academic supervision activities, principals guide teachers in compiling syllabi for each field of development at school or subjects at school based on content standards, competency standards and basic competencies usually in a school meeting.